Heat transfer in a circular tube fitted with free-spacing snail entry and conical-nozzle turbulators - Promvonge, P.; Eiamsa-ard, S. (My University, 2007)
The paper presents the effect of a free-spacing snail entry together with conical-nozzle turbulators on turbulent heat transfer and friction characteristics in a uniform heat-flux tube. The insertions of the conical or converging nozzle (C-nozzle) with different pitch ratios (PR) in common with the free-space snail entry are examined in a Reynolds number range from 8000 to 18000. A substantial augmentation of heat transfer for using the C-nozzles and snail entrance is expected by a strong influence from nozzle-induced reverse/re-circulation motion and snail-produced vortex/swirl motion for high Reynolds number. The experimental result shows a considerable increase in friction factor and heat transfer over the plain tube under the same operation conditions. Over the range investigated, the Nusselt numbers for employing both the enhancement devices with PR = 2.0, 4.0 and 7.0 are found to be higher than that for the plain tube around 315%, 300% and 285% respectively. The results obtained are correlated in the form of Nusselt number as a function of Reynolds number, Prandtl number and pitch ratio. For performance comparison at equal pumping power, both the enhancement devices with the smallest pitch ratio perform the best, especially at low Reynolds number. The present results are also compared with correlations obtained from similar enhancement devices but without free-spacing entry. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Enhancement device; Heat transfer augmentation; Re-circulation/reverse flow; Snail entry; Swirl flow; Turbulator